2020
DOI: 10.1002/cncy.22258
|View full text |Cite
|
Sign up to set email alerts
|

Determination of high‐risk HPV status of head and neck squamous cell carcinoma using the Roche cobas HPV test on cytologic specimens and acellular supernatant fluid

Abstract: BackgroundHigh‐risk human papillomavirus–positive (hrHPV+) oropharyngeal squamous cell carcinomas comprise a subset of head and neck squamous cell carcinomas (HNSCCs) with a distinct biology and prognosis. Commonly, the diagnosis of HNSCC is rendered on fine‐needle aspiration (FNA). Because cell blocks may be insufficient for determining HPV status using microscopy‐based techniques, the ability of liquid‐based assays was examined in the current study.MethodsThe performance of the Roche cobas 4800 platform was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…Two prior studies have found that the FNA supernatant holds promise as a potential substrate for determining HPV in patients with head and neck cancer 14,22 . Likewise, we found that even the FNA leftover wash component that is generally discarded as useless waste actually represents a rich resource of DNA for HPV analysis.…”
Section: Discussionsupporting
confidence: 61%
“…Two prior studies have found that the FNA supernatant holds promise as a potential substrate for determining HPV in patients with head and neck cancer 14,22 . Likewise, we found that even the FNA leftover wash component that is generally discarded as useless waste actually represents a rich resource of DNA for HPV analysis.…”
Section: Discussionsupporting
confidence: 61%
“…Nine studies evaluated HPV testing in formalin-fixed paraffin-embedded (FFPE) tissue [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], and five studies evaluated HPV detection in fine needle aspiration (FNA) [ 30 , 31 , 32 , 33 , 34 ]. Reference methods varied between studies; seven studies used p16 IHC as reference [ 24 , 25 , 27 , 30 , 33 , 34 ], three studies used HPV RNA as reference, where one study detected HPV RNA by ISH [ 22 ] and the other two studies detected HPV RNA by PCR [ 23 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies evaluated HPV testing in formalin-fixed paraffin-embedded (FFPE) tissue [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], and five studies evaluated HPV detection in fine needle aspiration (FNA) [ 30 , 31 , 32 , 33 , 34 ]. Reference methods varied between studies; seven studies used p16 IHC as reference [ 24 , 25 , 27 , 30 , 33 , 34 ], three studies used HPV RNA as reference, where one study detected HPV RNA by ISH [ 22 ] and the other two studies detected HPV RNA by PCR [ 23 , 26 ]. Another three studies used HPV DNA by PCR [ 28 , 29 , 32 ] as reference and finally, two studies combined two detection methods for reference; p16 IHC combined with HPV DNA PCR [ 21 ] and p16 IHC combined with HPV DNA PCR and/or HPV E6 seropositivity [ 31 ], respectively ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Data from a validation study on oral cytobrushes and FFPE samples indicate that the Cobas assay is highly sensitive for detecting low copy numbers of viral DNA and displays high repeatability and reproducibility for detection of HPV in oral samples 17 . A clinical evaluation of the Cobas assay also demonstrated comparable performance to the gold standard p16 immunohistochemistry assay for detection of HPV in cytological preparations from head and neck cancer patients 18 …”
Section: Discussionmentioning
confidence: 97%